"Re-building Greensburg" - Klein, Melanie (Kansas State University, 2009)
Citizens of Greensburg, Kansas say opportunity [1] emerged from tragedy when a May 2007 tornado leveled ninety-five percent of their rural community. The "opportunity" was to have a community-driven document that reflects rebuilding priorities expressed by the citizens, a Long Term Community Recovery Plan, LTCRP. The LTCRP priorities are laden with the term "sustainability," and encourage "a concentration of LEED® Platinum buildings" (FEMA, 2007, p. 17). However, neither the LEED® rating system credits required to reach Platinum Certification nor associated costs are explained in the LTCRP. This presentation of a research-guided design project reviews the process and product of a multi-disciplinary academic studio that provided design conceptualizations based upon Greensburg's LTCRP. All student designers addressed issues of ecological ethics as they pursued conceptualizations based on ecologically sustainable building practices. The studio produced visually-rich design conceptualizations intended to help a non-practitioner begin to understand the jargon of LEED®. This work was shared with Greensburg citizens through a grant from the KSU Center for Engagement and Community Development. First, the presentation introduces the context to which the student work responds: citizen input and the setting of post-tornado Greensburg. Second, the research and design processes which caused students to consider ecological ethics are reviewed. There were several instances where students felt ethically inclined to pursue standards beyond the LEED® rating system. Third, the presentation reviews the products of the academic studio. Because the citizens mandated LEED® Platinum ratings, the products of the academic studio are visually-rich design conceptualizations intended to help a non-practitioner begin to understand the jargon of LEED®. These studio products were intended to serve as catalysts for conversation as Greensburg pursues the next stages of physical planning and design. Finally, the presentation concludes with reflections on the design products, lessons learned and additional conversations that might have been addressed. [1] The vision statement "Blessed with a unique opportunity to create a strong community devoted to family, fostering businesses, working together for future growth" reflects the overall perspective of the community as developed at a Vision Retreat held August 1, 2007 (Federal Emergency Management Agency [FEMA], 2007, pg.1)
Keywords: Community vision; Student communication; Sustainability; Community engagement; Greensburg (Kan.); Leadership in Energy and Environmental Design Green Building Rating System